Game theory modeling for vehicle-pedestrian interactions and simulation based on cellular automata - Wu, Wenjing (2021)
In order to study the effect of crossing pedestrians on traffic performance at crosswalk without signal control, the work develops a game theory-based description of pedestrian-vehicle interactions, considering the decision-making uncertainty. The hybrid strategy of the game is obtained. The relevant parameters of the game model are calibrated by collected video data. The cellular automaton simulation system composed of a two-way four-lane traffic flow and pedestrian flow is constructed with the game model imbedded for identifying the effect of crossing pedestrians on traffic performance. The influencing factors are identified with their correlation analyzed by numerical simulation of different traffic conditions. According to the simulation results, the arrival rate of pedestrians has a great impact on traffic volume and pedestrian delay. The severity of conflicts between vehicles and pedestrians is classified and the causes are identified by analyzing the arrival rate of pedestrians and vehicles, respectively, and their relationship between one another. In addition, the threshold of traffic flow and pedestrian flow causing traffic conflicts and delay is proposed, also including the threshold of pedestrian arrival rate which will induce force crossing behaviors. The results show that the proposed model reconstructs the traits of traffic and pedestrian flow and their conflicts phenomenon at crosswalks. It provides some practical references for transportation agencies to meet pedestrians time-cost and comfort needs in crossing streets when they design pedestrian crossing facilities.